A longitudinal study of neuromelanin-sensitive magnetic resonance imaging in Parkinson's disease. (28th October 2016) - Matsuura, Keita; Maeda, Masayuki; Tabei, Ken-ichi; Umino, Maki; Kajikawa, Hiroyuki; Satoh, Masayuki; Kida, Hirotaka; Tomimoto, Hidekazu
Highlights: The SNc of Nueromelanin-sensitive MRI in PD reduced by year by year. The SNc in Nueromelanin-sensitive MRI negatively correlated with disease duration. We indicate that the analyses methods of NMI is reliable. Abstract: Purpose: Neuromelanin-sensitive MR imaging (NMI) is an increasingly powerful tool for the diagnosis of Parkinson's disease (PD). This study was undertaken to evaluate longitudinal changes on NMI in PD patients. Methods: We examined longitudinal changes on NMI in 14 PD patients. The area and contrast ratio (CR) of the substantia nigra pars compacta (SNc) were comparatively analyzed. Results: The total area and CR of the SNc upon follow-up NMI were significantly smaller than those on initial NMI (from 33.5 ± 18.9 pixels and 6.35 ± 2.86% to 21.5 ± 16.7 pixels and 4.19 ± 2.11%; Wilcoxon signed-rank test, p < 0.001 and p = 0.022, respectively). The area and CR of the dominant side SNc upon initial NMI were significantly greater than those on follow-up NMI (from 15.3 ± 9.1 pixels and 6.5 ± 2.7% to 7.9 ± 8.5 pixels and 3.7 ± 2.9%; Wilcoxon signed-rank test, p = 0.002 and p = 0.007, respectively). On a case-by-case basis, the area of the SNc invariably decreased upon follow-up NMI in all patients. We further demonstrated that the total area and CR of the SNc negatively correlated with disease duration (Pearson correlation coefficient, r = −0.63, p < 0.001 and r = −0.41, p = 0.031, respectively). In area analyses, our results demonstrated very high intraclass correlation coefficients for both intra- and inter-rater reliability. Conclusion: NMI is a useful and reliable tool for detecting neuropathological changes over time in PD patients.